MENENTUKAN MINIMUM MISCIBLE PRESSURE CO2 FLUIDA RESERVOIR LAPANGAN C SUMUR D MENGGUNAKAN APLIKASI CMG - Danera, Furqanorifki El; Hartono , Kartika Fajarwati; Oetomo , Hari Karyadi (Komunitas Menulis dan Meneliti (Kolibi), 2024)
Determining the Minimum Miscible Pressure (MMP) is a crucial step in planning and implementing Enhanced Oil Recovery (EOR) projects using CO2 injection. This study aims to determine the MMP value using the multiple contact method with a multiple mixing-cell calculation system in CMG WinProp software. This approach offers advantages in terms of time and cost efficiency compared to conventional experimental methods. The methodology involves modeling reservoir fluid using the Equation of State (EOS), followed by a PVT matching process. The accuracy of the EOS model is validated by comparing WinProp simulation results against laboratory test data, focusing on differential liberation and constant composition expansion. This matching process aims to minimize the margin of error between simulation results and experimental data. The research results the Minimum Miscible Pressure is identified at 2718.9 psia. These findings provide valuable insights into the pressure conditions required to achieve miscibility between CO2 and oil reservoir.